Gender and ethnicity in post-conflict Kosovo - Sumon Kumar Bhaumik; Ira N. Gang; Myeong-Su Yun (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
The paper examines the comparative economic wellbeing of female- and male-headed households among Serbs and Albanians in post-conflict Kosovo. Evidence from the living standards measurement study (LSMS) household survey, 2001, shows that Serb households, both those headed by women and men, are worse off than Albanians households. We find that female-headed households do not generally suffer more than male-headed households, but there is substantial variation among ethnic groups. While Albanian female-headed households are marginally better-off than Albanian maleheaded households, Serb female-headed households have the lowest standard of living.
Keywords: I32; O12; J15; 330; consumption; ethnicity; gender; Verbraucherausgaben; Geschlecht; Ethnische Gruppe; Serben; Albaner; Kosovo